Traditional male circumcision in eastern and southern Africa: a systematic review of prevalence and complications - Andrea Wilcken; Thomas Keil; Bruce Dick (The World Health Organization, 2010)
OBJECTIVE: To systematically review studies on the prevalence and complications of traditional male circumcision (i.e. circumcision by a traditional provider with no formal medical training), whose coverage and safety are unclear. METHODS: We systematically searched databases and reports for studies on the prevalence and complications of traditional male circumcision in youth 10-24 years of age in eastern and southern Africa, and also determined the ages at which traditional circumcision is most frequently performed. FINDINGS: Six studies reported the prevalence of traditional male circumcision, which had been practised in 25-90% of all circumcised male study participants. Most circumcisions were performed in boys 13-20 years of age. Only two of the six studies on complications reported overall complication rates (35% and 48%) following traditional male circumcision. The most common complications were infection, incomplete circumcision requiring re-circumcision and delayed wound healing. Infection was the most frequent cause of hospitalization. Mortality related to traditional male circumcision was 0.2%. CONCLUSION: Published studies on traditional male circumcision in eastern and southern Africa are limited; thus, it is not possible to accurately assess the prevalence of complications following the procedure or the impact of different traditional practices on subsequent adverse events. Also, differences in research methods and the absence of a standard reporting format for complications make it difficult to compare studies. Research into traditional male circumcision procedures, practices and complication rates using standardized reporting formats is needed.